IMPROVING THE MOTIVATION OF IPS LEARNING THROUGH ROLE PLAYING STRATEGIES IN BASIC SCHOOL STUDENTS - Mulyadi . (Jurnal Education and Development, 2021)
This study aims to increase social studies learning motivation through role playing strategies in grade IV elementary school students. The classroom action research has four stages, namely the planning stage, the implementation stage, the observation stage and the reflection stage which are carried out in two cycles. This study chose the subject of fourth grade students of SDN 170 / IX Marga. Data collection techniques in this study were carried out through interviews, observation, documentation, and field notes. Data analysis in this study used the interactive analysis model technique of Miles and Huberman. The results showed that there was an increase in student motivation as a result of using the role playing method.